2021
DOI: 10.1177/08982643211015027
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects on Loneliness of a Computer-Tailored Intervention for Older Adults With Chronic Diseases: A Randomized Controlled Trial

Abstract: Objectives: This study explores the effects of the Active Plus intervention aiming to decrease loneliness among older adults (>65 years) with chronic diseases. Methods: A randomized controlled trial (RCT) was performed (N = 585; age: M = 74.5 years, SD = 6.4), assessing loneliness at baseline, 6 months and 12 months. Outcome measures in the multilevel linear regression analyses were total, social and emotional loneliness. Results: At 12 months, significant decreases in total ( B = −.37, p = .01) and social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 74 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…The intervention expands and complements the existing Active Plus (and Active Plus65) physical activity intervention. While Active Plus effectively improved physical activity and reduced loneliness (27,29,53), the original intervention did not su ciently address the speci c needs of older adults in a low SEP (54). This was due to the fact that Active Plus primarily (and solely) focused on improving physical activity and, therefore, did not employ an integral or holistic approach, whereas the latter seems to resonate well with individuals in a low SEP (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intervention expands and complements the existing Active Plus (and Active Plus65) physical activity intervention. While Active Plus effectively improved physical activity and reduced loneliness (27,29,53), the original intervention did not su ciently address the speci c needs of older adults in a low SEP (54). This was due to the fact that Active Plus primarily (and solely) focused on improving physical activity and, therefore, did not employ an integral or holistic approach, whereas the latter seems to resonate well with individuals in a low SEP (21).…”
Section: Discussionmentioning
confidence: 99%
“…First, Active Plus improved short-and long-term physical activity in adults aged 50 years and over (27,53). Additionally, a recent study reported by Boekhout et al demonstrated that Active Plus (or Active Plus65; mainly designed for older adults) signi cantly reduced overall loneliness, based on the effects of social loneliness, amongst single, independently living older adults with chronic diseases (29). However, Active Plus by itself remained insu cient to improve physical activity in vulnerable older adults aged 65 years or older (54).…”
Section: Active Plus As a Foundation For Intervention Developmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Web-based interventions are a second option and can be used to deliver different content to individuals. It is possible to implement group interventions via videoconferencing apps (e.g., Zoom) in which therapeutic techniques and skills are being taught [35 ▪▪ ] or to address cognitive functioning and increase physical activity while also providing computer-tailored advice to reduce loneliness (the Active Plus program) [36 ▪▪ ]. Both programs deliver evidence-based therapeutic techniques that previously have shown to reduce loneliness [37].…”
Section: Promising Interventions For Reducing Lonelinessmentioning
confidence: 99%
“…Because of the high prevalence of loneliness, its effects on health, and increasing evidence that interventions may reduce loneliness, 10,15–18 clinical screening for loneliness among older adults may be warranted 2 . For older adults who receive health insurance through the Medicare Advantage program, annual wellness visits, required by the Centers for Medicare and Medicaid Services (CMS) since 2011, provide an opportunity to screen for loneliness and other health concerns 19 .…”
Section: Introductionmentioning
confidence: 99%